EFFECT OF LOW PROTEIN DIETS SUPPLEMENTED WITH AMINO ACIDS ON PRODUCTIVE PERFORMANCE, CARCASS YIELD AND INTESTINAL INTEGRITY ON BROILERS - Adriana Hernández-Huesca; Arturo Cortes-Cuevas; Mireya Juarez-Ramirez; José Menocal-Arce; Melanie Margarito-Romero; Ernesto Ávila-Gonzalez (Tropical and Subtropical Agroecosystems)
Background. A global approach in the development of diets low in crude protein (CP) supplemented with amino acids is to obtain productive yields similar to standard diets. Objective. To evaluate the reduction of CP in diets with similar amounts of Methionine, Lysine, Threonine, Valine, Arginine, and Tryptophan and to measure its effect on the productive performance, carcass yield and intestinal integrity. Methodology. 882 mixed Ross chickens from 1 to 49 days were used in a 2X3 factorial arrangement; one factor was sex (male and female) and another 3 PC levels (0, 1 and 2% less), each treatment had 6 replicates of 25 chickens each. Results. The results indicated similar (P>0.05) productive and carcass performance with the different protein levels. Females showed a higher percentage of abdominal fat compared to males (P<0.05). The decrease in protein increased the percentage of abdominal fat (P<0.05). For intestinal villi, the length of the villi was greater (P<0.05) in males compared to females. For crypt depth, there was no difference (P>0.05) in the sex factor or the protein factor. Implications. PC reduction lowers costs and reduces nitrogen pollution. Conclusion. It is concluded that diets reduced in CP supplemented with amino acids do not affect productivity, carcass performance and intestinal integrity.